2016
DOI: 10.1159/000444661
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Levels of IL-6, sE-Selectin and Distal Sensory Nerve Conduction Studies in Patients with Prediabetes

Abstract: Aim: To determine the association between interleukin-6 (IL-6) and soluble E-selectin (sE-selectin) levels with the electrodiagnostic abnormalities in patients with impaired fasting glucose (IFG) and impaired glucose tolerance (IGT). Methods: Serum HbA1c, C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), fibrinogen, IL-6 and sE-selectin levels were analyzed in 25 IFG patients, 22 IGT patients and 41 controls. Nerve conduction studies (NCS) of sural, dorsal sural (DS), medial dorsal cutaneous and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Another study reported an association between elevated levels of IL-6 and CRP and the risk of developing T2DM in the future and the link remained significant following adjustment for BMI, family history of diabetes, smoking, exercise and alcohol use using multivariate analysis [4]. More recently, studies have shown that HbA1c and IL-6 levels were significantly higher in IFG and IGT patients when compared to healthy individuals [11,12].…”
Section: Current Research In Diabetes and Obesity Journalmentioning
confidence: 99%
“…Another study reported an association between elevated levels of IL-6 and CRP and the risk of developing T2DM in the future and the link remained significant following adjustment for BMI, family history of diabetes, smoking, exercise and alcohol use using multivariate analysis [4]. More recently, studies have shown that HbA1c and IL-6 levels were significantly higher in IFG and IGT patients when compared to healthy individuals [11,12].…”
Section: Current Research In Diabetes and Obesity Journalmentioning
confidence: 99%
“…Recently, we have shown corneal nerve loss in patients with TIA 23 , acute ischemic stroke 24 27 and recurrent stroke 28 . Increased plasma adhesion molecules including P-selectin and ICAM-1 predict the development of diabetic neuropathy 29 and elevated IL-6 has been associated with distal neuropathy in subjects with impaired glucose tolerance 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown a signi cant loss of corneal nerves in patients with TIA [23], acute ischemic stroke [24][25][26] and recurrent stroke [27] indicating that it may be a surrogate marker for the risk of stroke. Increased plasma adhesion molecules including P-selectin and ICAM-1 predict the development of diabetic neuropathy over 5 years [28] and elevated IL-6 has been associated with distal neuropathy in subjects with impaired glucose tolerance [29].…”
Section: Introductionmentioning
confidence: 99%